Wartości sakralne jako przeciwwaga ideologizacji szkoły w czasopiśmie "Polonistyka" w latach 1991-2015 = Sacral values as counterpoise for ideologization of school`s system in the magazine "Polonistyka" in years 1991-2015 - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article of Anastazja Seul ?Sacral values as counterpoise for ideologization of school`s system in the magazine ?Polonistyka? in years 1991-2015? portrays religious issues present within articles in this particular magazine for teachers of Polish language and literature. That was the time when editor-in-chief`s position was held by Bożena Chrząstowska who made sure that sacral values were always mentioned in the magazine. It was her own way to compensate the negligence that was a result of ideologization of ?Polonistyka? during times of communism in Poland. After year 1991, the magazine presents sacrum as one of the most important elements of European culture, including Polish literature.
Keywords: aksjologia; ideologia; szkoła; sacrum; literatura piękna; Chrząstowska, Bożena (1929-); Polonistyka - czasopismo; axiology; ideology; school; belles-lettres